Genetic Diversity of Oil Palm Population Planting in Khokpho, Pattani with Microsatellite Technique - นิคม จารุ; ดอฮา ซัมซูรี; อำบูเล็ง รอวีย๊ะ (YRU Journal of Science and Technology, 2018)
The objective in this study is that observes oil palm genetic variation with Microsatellite marker technique. 10 samples of DNA extraction from young leaf in Khopho, Pattani were amplified with 10 primers and observed by agarose gel electrophoresis method. The microsatellite fragments were analyzed with MEGA program and calculated genetic diversity by Arlquin Program. The UPGMA dendrogram in these results represent genetic relationship clades in only one group. Nucleotide diversity and Haplotype diversity values indicate that non genetic variation in theses samples. From these results indicate that have not different genetic variation in population in Khopho sample. This study might show that Microsatellite marker technique able to analyze genetic variation diversity in oil palm plant population in Khopho, Pattani.